2020
DOI: 10.1002/ange.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Boosted Charge Storage on Heteroatom‐Doped Carbons

Abstract: Although tremendous efforts have been devoted to understanding the origin of boosted charge storage on heteroatom‐doped carbons, none of the present studies has shown a whole landscape. Herein, by both experimental evidence and theoretical simulation, it is demonstrated that heteroatom doping not only results in a broadened operating voltage, but also successfully promotes the specific capacitance in aqueous supercapacitors. In particular, the electrolyte cations adsorbed on heteroatom‐doped carbon can effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…44 The presence of heteroatoms in the graphene sheets bolsters charge accumulation at their sites, in the case of both oxygen and nitrogen conjugated species. 85 The site provides a higher negative potential on the Allen electronegativity scale compared to carbon, thus inducing preferred oxidation of Cu ions during electroplating and passivating the heteroatom charge. This was confirmed by the reduction of heteroatom species observed in XPS C 1s peaks in Figure 4D and by the shift of the O 1s spectrum toward CuO and Cu 2 O species reducing contribution from a hydroxyl functional group (Figure 4E).…”
Section: Discussionmentioning
confidence: 99%
“…44 The presence of heteroatoms in the graphene sheets bolsters charge accumulation at their sites, in the case of both oxygen and nitrogen conjugated species. 85 The site provides a higher negative potential on the Allen electronegativity scale compared to carbon, thus inducing preferred oxidation of Cu ions during electroplating and passivating the heteroatom charge. This was confirmed by the reduction of heteroatom species observed in XPS C 1s peaks in Figure 4D and by the shift of the O 1s spectrum toward CuO and Cu 2 O species reducing contribution from a hydroxyl functional group (Figure 4E).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the co‐desorption of H + (Figure 3a), Na + (Figure 3b) and K + (Figure 3c) on N, P, and O triple‐doped graphene were simulated. The Na + and K + adsorption structures with the smallest chemical adsorption energy were used to adsorb protons (Figure 3d) [27d] . It was found that hydrogen adsorption energy increased from 0.07 eV to 0.13 eV for Na + pre‐adsorption, while for K + pre‐adsorption, hydrogen adsorption energy increased from 0.07 eV to 0.16 eV (Figure 3e).…”
Section: Regulation Strategies For Electrodementioning
confidence: 99%
“…Unfortunately, the practical application of SCs has been limited by their low energy density [4][5][6]. According to the equation E = 0.5CV 2 (where E, C, and V are the energy density, specific capacitance, and voltage window of the devices, respectively), numerous materials have been developed to increase the specific capacitance, with the aim of improving the energy density [7][8][9]. In contrast to the specific capacitance, the energy density is proportional to the square of the cell voltage.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with organic electrolytes with flammability and low conductivity properties, aqueous electrolytes with a sufficiently high working voltage window are considered to be an appropriate alternative to organic electrolytes [16]. In recent years, numerous materials have been designed to increase the voltage window of aqueous electrolyte SCs (AESCs), such as polyanionic molybdenophosphate [17], heteroatom-doped carbon [9], and alkali cation-doped manganese oxide [18][19][20]. These materials can effectively inhibit the occurrence of the hydrogen evolution reaction or oxygen evolution reaction in a charging-discharging process [21].…”
Section: Introductionmentioning
confidence: 99%